Development of a photo-catalytic converter for potential use in the detoxification of Cr(vi) metal in water from natural resources. Issue 8 (7th February 2018) - Kar, Prasenjit; Maji, Tuhin Kumar; Sarkar, Probir Kumar; Lemmens, Peter; Pal, Samir Kumar
Abstract : Copper-porphyrin sensitized nanoporous TiO2 microsphere is decorated on a stainless steel mesh for photocatalytic conversion of carcinogenic Cr 6+ to non-toxic Cr 3+ and physical filtration. Abstract : Porphyrin dye sensitized nanomaterials (nanohybrids) are advantageous for application in photocatalysis due to their additional absorption band that matches the solar irradiance spectrum. Here we have impregnated protoporphyrin IX with copper(ii ) ions and sensitized porous TiO2 microspheres (∼1.5 μm in diameter) in order to synthesize a functional nanohybrid for application in visible light photocatalysis. While electron microscopy studies (FESEM and HRTEM) confirm the inorganic porous structure of the microspheres, Fourier transform infrared (FTIR), electronic spectroscopy and picosecond resolved fluorescence studies on the sensitizing PP molecules reveal the formation of the functional nanohybrid. Hexavalent chromium (Cr(vi )) in the aquatic environment is a commonly identified proven carcinogenic heavy metal pollutant, whereas Cr(iii ) is nontoxic and considered to be an essential nutrient for living organisms. We have applied the nanohybrid for an efficient reduction of toxic Cr(vi ) metal ions to non-toxic Cr(iii ) in water under visible light illumination. The advantage of the Cu ion impregnation into the sensitizing PP dye is evident from the intact efficacy in the photocatalytic reduction in the presence of water dissolved metal ions (Cr 3+ and Fe 3+ ) is confirmed from our study. On the other hand, the nanohybrid without the Cu(ii ) suffers from interference from other dissolved metal ions during the photocatalytic reduction process. For a prototype application, we have developed an active filter (having physical and chemical filtering capability) by depositing the nanohybrid on an extended surface of a stainless-steel metal mesh (size 2 cm × 2 cm, pore size 150 μm × 200 μm). The prototype active filter exhibits significant potential for chemical filtering of toxic Cr(vi ) ions (photoreduction to Cr(iii )) along with physical cleaning of suspended particulates present in water.